PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KELURAHAN MUSTIKA JAYA KOTA BEKASI - Fildza Hulwani Karlina; Irene Mariane (Reformasi Hukum Trisakti, 2022)
The PTSL area will focus on Mustika Jaya in 2021. The issue is who is preventing the full implementation of systematic land registration in Mustika Jaya Village, Bekasi City, what challenges are being faced, and how these challenges might be solved. The study is normative in character and uses descriptive analysis research, which is based on secondary data. gathering information through interviews and book research, analyzing qualitative data, and drawing conclusions using a deductive logic process. The findings of the research conducted as part of the PTSL program in Mustika Jaya Village, Bekasi City, are in conformity with the land registration regulations. Inheritance issues that have not been settled and the absence of heirs are challenges. The Land Office uses deliberation as a form of mediation to address unresolved inheritance issues and agrees that the procedure can proceed again. If there is no agreement, the property is classified as disputed or problematic land, which prevents you from taking part in the full systematic land registration procedure. The Land Office assists distant heirs in receiving information from the absent heirs.